Pemberdayaan Pelaku Usaha Hidroponik Desa Berkoh Melalui Peningkatan Efektifitas Pembibitan - Afandi, Mas Aly; Purnama, Sevia Indah; Wibisono, Gunawan; Adriansyah, Bagas; Oktaviana, Lutvi Tri (Politeknik Negeri Cilacap, 2025)
Hydroponic entrepreneurs are one of the business sectors affected by extreme climate change in Indonesia. The main problem caused by extreme climate change is the uncertain seeding time. Buyers such as restaurants need a supply of fresh vegetables at a specific time. Uncertain seeding due to extreme weather makes farmers unable to supply fresh vegetables at the specified time. The community service that has been carried out aims to apply artificial lighting technology to speed up the 2-5 day seeding process by vegetable farmers. The community service carried out uses an empowerment method to utilize artificial lighting technology during the seeding process. Before using this technology, farmers needed 10-15 days depending on the sunlight conditions during that period. Based on the activities that have been carried out, artificial lighting technology can provide a consistent seeding time of 8-10 days. The results of the community service show that there has been an increase in empowerment among farmers in Berkoh village.